2021
DOI: 10.1001/jamaoncol.2021.2939
|View full text |Cite
|
Sign up to set email alerts
|

Single-Fraction vs Multifraction Stereotactic Ablative Body Radiotherapy for Pulmonary Oligometastases (SAFRON II)

Abstract: for the Stereotactic Ablative Fractionated Radiotherapy Versus Radiosurgery for Oligometastatic Neoplasia to the Lung (SAFRON) II Study Investigators IMPORTANCE Evidence is lacking from randomized clinical trials to guide the optimal approach for stereotactic ablative body radiotherapy (SABR) in patients with pulmonary oligometastases.OBJECTIVE To assess whether single-fraction or multifraction SABR is more effective for the treatment of patients with pulmonary oligometastases.DESIGN, SETTING, AND PARTICIPANTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 18 publications
4
51
0
1
Order By: Relevance
“…Nine studies met criteria for this analysis [10,11,16,[21][22][23][24][25][26]. Publication years ranged from 2003 to 2021.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies met criteria for this analysis [10,11,16,[21][22][23][24][25][26]. Publication years ranged from 2003 to 2021.…”
Section: Resultsmentioning
confidence: 99%
“…The phase II SAFRON II trial randomized 87 patients with 133 pulmonary metastases to either 28 Gy in a single fraction or 48 Gy in four fractions [16]. No significant differences were found between the multi-and single-fraction arms for freedom from local failure (95% versus 93%, p = 0.13), OS (95% versus 93%, p = 0.44), or median disease-free survival (13.2 versus 14.3 months, p > 0.99) [16].…”
Section: Lung Oligometastases: Local Control and Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, higher doses showed a trend towards better outcomes in this study [ 21 ]. Recent clinical trial data revealed that single-fraction SBRT is more effective than multi-fraction SBRT in pulmonary oligometastases [ 22 ]. This evidence supports the rationale for RRS treatment in the setting of renal cell carcinoma with pulmonary metastases.…”
Section: Discussionmentioning
confidence: 99%
“…A phase 3 randomized trial showed that the local recurrence rate of single-dose 24 Gy radiotherapy was lower than that 27 Gy SBRT in three fractions, with no significant difference in toxicity ( 25 ). However, the results of a phase 2 randomized trial (SAFRON II) published in August 2021 demonstrated that SABR with a single 28-Gy fraction and four fractions of 12 Gy for lung oligometastases yielded comparable outcomes ( 26 ).…”
Section: Discussionmentioning
confidence: 99%